The mechanism of high mobility group box-1 protein and its bidirectional regulation in tumors (Biomolecules and Biomedicine, 2024)
High-mobility group box-1 protein (HMGB1) is a nonhistone chromatin-related protein widely found in eukaryotic cells. It is involved in the transcription, replication, and repair of DNA to maintain nuclear homeostasis. It participates in cell growth, differentiation, and signal transduction. Recent studies showed that HMGB1 has a bidirectional regulatory effect on tumors by regulating TLR4/MYD88/NF-κB and RAGE/AMPK/mTOR signaling pathways. On the one hand, it is highly expressed in a variety of tumors, promoting tumor proliferation and invasion, while on the other hand, it induces autophagy and apoptosis of tumor cells and stimulates tumor-infiltrating lymphocytes to produce an anti-tumor immune response. At present, HMGB1 could be used as a target to regulate the drug resistance and prognostication in cancer. Clinical applications of HMGB1 in cancer need further in-depth studies.